Low‐intensity pulsed ultrasound promotes the formation of periodontal ligament stem cell sheets and ectopic periodontal tissue regeneration. Issue 7 (30th September 2020) - Li, Han; Zhou, Jie; Zhu, Mengyuan; Ying, Siqi; Li, Lingjie; Chen, Duanjing; Li, Jie; Song, Jinlin
Abstract: Human periodontal ligament stem cells (hPDLSCs) sheets play an important role in periodontal tissue engineering. Low‐intensity pulsed ultrasound (LIPUS) has been reported as an effective stimulus to regulate cell biological behavior. The present study aims to explore the potential of LIPUS to promote the formation and function of hPDLSC sheets (hPDLSCSs). Hematoxylin–eosin (H&E) staining, western blot, real‐time PCR, alkaline phosphatase (ALP), and alizarin red staining were used to evaluate the formation and osteogenic effect of LIPUS on hPDLSCSs in vitro . Hydroxyapatite with or without hPDLSCSs was transplanted in the subcutaneous pockets on the back of nude mice and histological analysis was performed. H&E staining showed increased synthesis of extracellular matrix (ECM) and real‐time PCR detected a significant increase in ECM‐related genes after LIPUS treatment. In addition, LIPUS could promote the expression of osteogenic differentiation‐related genes and proteins. ALP and alizarin red staining also found LIPUS enhanced the osteogenesis of hPDLSCSs. After transplantation in vivo, more dense collagen fibers similar to periodontal ligament were regenerated. Collectively, these results indicate that LIPUS not only promotes the formation and osteogenic differentiation of hPDLSCSs but also is a potential treatment strategy for periodontal tissue engineering.